Performance Evaluation of Pulse Position Modulation Scheme in Automatic Dependent Surveillance Broadcast System - Hassan, Khalid; Abdallah, Mohamed (University of Khartoum Engineering Journal, 2022)
this paper presents a new formula for calculating the Bit Error Rate (BER) and the Packet Error Rate (PER) for binary pulse position modulation scheme which had been used in Automatic Dependent Surveillance Broadcast (ADS-B) system, ADS-B system is used in air traffic surveillance and control. ADS-B system uses the Binary Pulse Position Modulation (BPPM) scheme in the link between the aircraft and the ground station. The results show that the simulated bit-error rate and packet error rate are approximately matches the theoretical one; these results have been obtained for both coherent and non-coherent detection. As a result, mathematical formulas to represent the probability of error for BPPM are also derived for both coherent and no-coherent detection scheme.